An examination of the knowledge resources used by U.P. History researchers in infromation-seeking - Apuli, Laila L. (2004)
This study examined the knowledge resources employed by the University of the Philippines history researchers in their information related tasks at the UP Main Library Filipiniana sections. It investigated how these knowledge resources were used and helped them in information-seeking. The study aims to support the move of developing a user-centered information system and services that would closely tailor to the needs of the history researchers.